Desentralisasi Pendidikan melalui Kurikulum Muatan Lokal dalam Menjaga Kearifan Lokal di Dinas Pendidikan Provinsi Sumatra Utara - Sazkya, Alya; Trimurni, Februati (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
Decentralization of education empowers the North Sumatra Provincial Education Office to develop a local content curriculum to preserve local wisdom amidst the currents of modernization and globalization. However, its implementation faces obstacles such as limited resources, low stakeholder participation, and a lack of school and teacher preparedness. This study aims to describe the implementation of educational decentralization through a local content curriculum in preserving local wisdom. The method used is descriptive qualitative with informants from the Education Office officials, principals, teachers, students, and parents. The analysis uses the Lindblom incremental model with three indicators: adjustment to community needs, continuous renewal, and actor participation. The results show that the normative authority of the provincial government has not been optimal. Some high schools do not implement local content due to a lack of policy socialization. Implementation is more through the Pancasila Student Profile Strengthening Project (P5) from the central government. Information transparency, provision of adequate resources, and increased community participation are needed for educational decentralization to effectively preserve local wisdom in North Sumatra.